CHARACTER EDUCATION IN ENGLISH LANGUAGE LEARNING: AN ANALYSIS OF CHARACTER VALUES IN THE ENGLISH FOR NUSANTARA TEXTBOOK FOR GRADES III–VI ELEMENTARY SCHOOL - Zahwa Rizky Aulia; Ria Angraini (University of Kuningan, 2026)
Character education has been positioned as a foundational objective of Indonesian elementary education, particularly under the Kurikulum Merdeka framework, which emphasizes the development of the Pancasila Student Profile. While prior scholarship acknowledges the strategic role of textbooks in mediating value formation, empirical analyses examining how character dimensions are systematically represented in elementary English as a Foreign Language (EFL) materials remain limited. This study aims to answer the following research questions: (1) What character values are represented in the English for Nusantara textbooks for Grades III–VI? (2) How are the six dimensions of the Pancasila Student Profile distributed across the textbooks? and (3) Which character dimensions are most and least dominant? This study investigates the extent to which character values are embedded in four English for Nusantara textbooks for Grades III–VI. Adopting a qualitative content analysis with a directed coding procedure, the study analyzed textual and visual components using the six dimensions of the Pancasila Student Profile as analytical categories. To complement the qualitative analysis, frequency counts and percentages were used to describe the distribution of character values. The findings indicate that character education is substantively integrated across grade levels; however, its representation is disproportionate. Critical Reasoning dominates the materials, followed by Independence and Mutual Cooperation, whereas Global Diversity is minimally represented. These patterns suggest a stronger orientation toward cognitive and behavioral competencies than toward intercultural development. The study underscores the need for a more balanced incorporation of character dimensions to ensure holistic value formation within elementary EFL instruction.